STATISTICAL STUDY TO SHOW THE IMPACT OF BANKING SYSTEM DEPOSITS ON THE GROSS DOMESTIC PRODUCT IN IRAQ DURING THE PERIOD (2005-2020) - Hayder Sabah Tuama; Ali Salman Tuama Alchaabawi (American Journals, 2023)
Monetary variables (bank deposits and cash credit) are considered important variables in monetary policy in developing and developed countries alike, especially by providing financing for the development process and providing cash liquidity needed by investment activity, but Iraq is the exception to that as it did not rely much on the commodity sectors in creating added value, because the economy depends on external variables, including the rentier resource coming from the extractive sector. Does monetary policy and the weak role of the central bank in economic activity in Iraq during the period (2005-2020), and statistical and standard tests were used that showed the presence of stability of the variables in the first difference, and the lack of self-correlation between the variables, and the heterogeneity of the variation between the studied variables, in addition To the substantiality of the model, which means the possibility of activating monetary policy in Iraq to influence economic activity.
Keywords: Bank Deposits, Cash Credit, Monetary policy, Error Correction vector